Does Transformative Digital Learning Management Enhance the Sustainability of Inclusive Islamic Education? Evidence from Diaspora Children in Australia - Maulidya Ulfah; Atikah Syamsi; Ema Wilianti Dewi; Ayu Luhanarky; Deni Hadiana (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
This study aims to analyze the influence of transformative digital learning management strategies on the sustainability of inclusive Islamic education for diaspora children in Australia. The quantitative approach used a survey design, involving 85 respondents consisting of parents, educators, and children of the Muslim diaspora in Sydney, Queensland, and Melbourne. The digital learning management aspects measured included planning, implementation, monitoring, and evaluation, as well as educational sustainability: accessibility, continuity, and the integration of Islamic values. Data analysis used PLS-SEM. The results showed that transformative digital learning management significantly influenced the sustainability of inclusive Islamic education (β = 0.68; p < 0.01), with support from the Muslim community and moderation. The planning and evaluation aspects proved the most dominant, while digital implementation increased children’s participation and strengthened inclusive Islamic values. Support from the Muslim community and local technology adaptation also played a role in expanding access and maintaining sustainability. These findings confirm that digital transformation in Islamic education management not only improves academic effectiveness but also supports the sustainability of inclusive and values-based education. In practice, this research provides recommendations to policymakers, educational institutions, and community organizations to develop digital learning models that are adaptive, sustainable, and aligned with Islamic values in a multicultural environment.